Serum total prostate-specific antigen values in men with symptomatic prostate enlargement in Nigeria: role in clinical decision-making - Nnabugwu II (Dove Medical Press, 2014)
Ikenna I Nnabugwu,1,2 Fred O Ugwumba,1 Oghenekaro A Enivwenae,2 Emeka I Udeh,1 Chris O Otene,2 Chinwe A Nnabugwu3 1Urology Unit, Department of Surgery, College of Medicine, University of Nigeria, Nsukka, 2Urology Unit, Department of Surgery, 3Department of Medical Laboratory Services, Federal Medical Centre, Asaba, Nigeria Background: Prostatic enlargement is a common cause of bladder outlet obstruction in men in Nigeria. Malignant enlargements must be differentiated from benign enlargements for adequate treatment of each patient. High serum total prostate-specific antigen (tPSA) levels suggest malignancy, but some of the biopsies done due to a serum tPSA value >4 ng/mL would be negative for malignancy because of the low specificity of tPSA for prostate cancer. This study aims to compare the histologic findings of all prostate specimens obtained from core needle biopsy, open simple prostatectomy, and transurethral resection of the prostate with the respective serum tPSA values in an attempt to decipher the role of serum tPSA in the management of these patients.Methods: The case notes of patients attended to from April 2009 to March 2012 were analyzed. Essentially, the age of the patient, findings on digital rectal examination, abdominopelvic ultrasonography report on the prostate, serum tPSA, and histology reports from biopsy or prostatectomy specimens as indicated were extracted for analysis.Results: The relationship between age, findings on digital rectal examination, serum tPSA, abdominopelvic ultrasonography report, and histology are compared. A statistically significant relationship existed between a malignant histology and age 65 years and older, suspicious findings on digital rectal examination, suspicious ultrasonography findings, and serum tPSA >10 ng/mL, but not tPSA >4 ng/mL.Conclusion: In Nigerian patients with symptomatic prostate enlargement, serum tPSA should be seen as a continuum with increasing risk of prostate malignancy. Keywords: serum total prostate-specific antigen, symptomatic prostate enlargement, prostate histology